Relationship between maternal obesity and pregnancy outcome - F Bakouei (Babol University of Medical Sciences, 2001)
Objective: This study was done to determine the role of maternal obesity on pregnancy outcome in pregnant women at Amol Imam Reza hospital. Methods: This study was done on 240 pregnant women in the age range 18-35 and at full term pregnancy with cephalic presentation of fetus that were equally divided into two groups (Women with normal weight (19.8≤BMI≤26) and obese women (BMI>26)). Their age, education, employment, parity, birth interval and their weight gain during pregnancy were equal in both groups. Data were gathered by questionnaires and then analyzed by statistical method. Findings: The mean duration of the first, third and the whole stages of delivery in obese group was more than other group. Also, the mean duration of second stage was equal in both groups. But, there was a significant difference between two groups in the mean of total duration of delivery stages relevant to their weight gain during pregnancy (Equal or more than 12kg). Oxytocin was used in obese women (64.2%) more than women with normal weight (44.4%). The mean of neonatal weight in obese women (3670.8±456.4 g) was significantly more than that of women with normal weight (3511.7±452.7 g). Conclusion: Pregnancy in obese women was considered as a high risk. Obese women should be under the care of a specialist during their pregnancy and delivery. In this way, duration of delivery stages and neonatal weight will be controlled.